MODUL LATIH INVERTER SEBAGAI KENDALI KECEPATAN MOTOR INDUKSI MENGGUNAKAN HMI BERBASIS PLC: Indonesia - Rachman, Faishal; Rahmadewi, Reni (Aisyah Journal Of Informatics and Electrical Engineering (A.J.I.E.E), 2023)
In the industrial world, we have definitely met with induction motors, both 1-phase and 3-phase voltage sources. Induction motors are widely used today, because they have simple construction, are inexpensive, relatively light, have high efficiency and are easy to maintain compared to DC motors. However, in terms of adjusting the speed and torque of this motor is not an easy problem, with the development of technology, this can be overcome by using an inverter. The inverter used is a Variable Speed Drive (VSD) Inverter type. This inverter can convert and regulate 3 phase voltage sources between 0 – 60 Hz depending on the specifications of the inverter used. In this study the ladder diagram program was designed using TIA Portal V15.1 on a Programable Logic Controller (PLC) which is used to control the speed of a 3 phase induction motor through the Human Machine Interface (HMI) which is connected to the inverter. The controlled frequency is 0 – 50 Hz and the resulting rotation is 0 – 1400 rpm. The greater the frequency data that is set, the speed of the induction motor will be faster.